2016
DOI: 10.4171/rmi/902
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Harnack estimates in slit domains and applications to thin free boundary problems

Abstract: Abstract. We provide a higher order boundary Harnack inequality for harmonic functions in slit domains. As a corollary we obtain the C ∞ regularity of the free boundary in the Signorini problem near non-degenerate points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 5 publications
(15 reference statements)
1
65
0
Order By: Relevance
“…Relying neither on frequency functions nor on comparison arguments, Andersson [And13] has shown that similar results also hold for the full Lamé system. Recently, Koch, Petrosyan and Shi [KPS14] as well as De Silva and Savin [DSS14] have proved smoothness ([KPS14] proved analyticity) of the regular free boundary. Moreover, Garofalo and Petrosyan [GP09] give a structure theorem for the singular set of the thin obstacle problem.…”
Section: Resultsmentioning
confidence: 98%
“…Relying neither on frequency functions nor on comparison arguments, Andersson [And13] has shown that similar results also hold for the full Lamé system. Recently, Koch, Petrosyan and Shi [KPS14] as well as De Silva and Savin [DSS14] have proved smoothness ([KPS14] proved analyticity) of the regular free boundary. Moreover, Garofalo and Petrosyan [GP09] give a structure theorem for the singular set of the thin obstacle problem.…”
Section: Resultsmentioning
confidence: 98%
“…In [2] they give a complete description of the blow-up limits at the points of frequency 3 =2 and prove that the regular free boundary Reg.u/ is locally a .d 2/-dimensional C 1;˛h ypersurface in R d 1 . Later the regular part of the free boundary has been shown to be C 1 in [6] and analytic in [17] (see also [16,18]), and analogous results were extended to more general fractional Laplacian (see [4]), of which the thin obstacle is a particular example. Garofalo and Petrosyan (cf.…”
Section: State Of the Artmentioning
confidence: 84%
“…Remark 1.4. Besides its own interest, sharp boundary regularity estimates find usually applications in free boundary problems; see for example [DS16]. We think that the ideas introduced in this paper could be used in order to establish the higher regularity of free boundaries in the obstacle problem for the fractional Laplacian, at least in case s > 1/2; see [BFR17].…”
Section: Introductionmentioning
confidence: 92%